Exploring the Impact of Facebook Usage on Nepali Users: A Survey Study Conducted on the Facebook Platform (Quest Journal of Management and Social Sciences, 2024)
Background: Facebook significantly influences Nepal's social interactions, psychological well-being, and cultural norms. Given its wide adoption among Nepali users, understanding its effects within the diverse socio-cultural context, especially among youth, is essential.Objective: This study aims to assess how Facebook impacts Nepali users' social interactions, psychological well-being, and cultural expression, guiding evidence-based interventions and policies promoting responsible social media use in Nepal.Method: This quantitative study collects data from Nepali users using an online survey exclusively on Facebook. Stratified random sampling (minimum 384 respondents) ensures demographic diversity. SPSS analyses data using descriptive statistics for demographic profiles and Facebook usage patterns. Inferential statistics (correlation, regression) explore relationships between Facebook usage and impacts.Results: Preliminary findings show that diverse Facebook usage patterns among Nepali users affect social interactions and psychological well-being. Correlational analysis indicates links between usage intensity and specific outcomes. Qualitative insights reveal cultural themes in online interactions.Conclusion: The study highlights the nuanced impact of Facebook in Nepal, emphasizing the need for targeted interventions. By comprehending these effects, policymakers can create effective strategies that harness Facebook's advantages while mitigating risks, ultimately promoting healthier social media engagement in Nepal.